Analisis Faktor-Faktor yang Mempengaruhi Produksi Nanas (Ananas Comocuc) dan Komoditi Lokal yang Diaplikasikan Petani Nanas di Kecamatan Mattiro Bulu, Kabupaten Pinrang - Irmayani, Irmayani; Risdayanti, Risdayanti; Arman, Arman (Jurnal Saintifik (Multi Science Journal), 2024)
Pineapple is one of Indonesia's export commodities, according to BPS data by 2022 the production of pineapples in Indonesia reached 3.2 million tons, which is a 10.98% increase compared to the previous year. Pineapple production in Indonesia is supported by many areas in Indonesia that are the site of pineapples production, one of the pines producing areas is South Sulawesi precisely in the village of Bottae, Mattiro Bulu district of Pinrang district. The village of Bottae is a village that has local potential in pineapple farming supported by the natural conditions suitable for planting ananas trees, given the local potential there is a need for the role of pine apple farmers in exploiting it to support the survival of ananas farmers. The production of pineapple in Bottae Village is influenced by production factors such as land area, seedlings, capital, fertilizer, and labor, therefore, the purpose of this research is to 1) Identify the factors that affect the production of Pineapples in Bottas County Mattiro Bulu District of Pinrang, 2) Analyze how much the production factors that influence the production in the Bottaes District Mattiros Pinu District, Pinrang District, 3) Know the local commodities that are applied to the pine farmers in Buttas County mattiro bulu District. The research uses two methods, quantitative and descriptive with a qualitative approach, as well as data sources obtained through observations, interviews, questionnaires, and documentation. A total of 50 pineapple farmers samples and data processed using SPSS version 29 then using techniques of analysis of multiple linear regression, data gained through interviews will be described to obtain answers to the third problem. From the results of the research obtained: 1) Seeds, Capital, and Fertilizers have a significant influence on the production of pineapple in the Bottae village of Mattiro Bulu district of Pinrang, 2) The great strength of the factors affecting the production is 84.9%, 3) There is a process of seed preparation carried out by pine apple farmers alternately to meet the needs of pines seed in the Mattiros Bulu village of Pinang.